The little mermaid - Calmenson, Stephanie; Mateu, Francese (New York : Random House, 2006)
"Ariel is tired of living under the sea-she wants to be human and walk on land. She gets her chance after making a deal with an evil sea witch, but something's fishy! Can Flounder, Sebastian and Scuttle help make the Little Mermaid's dream come true?"--Cover.
At head of title: Disney's.
Keywords: Children's stories